Nursing Students’ Attitudes towards Immigrants’ Social Rights - Sánchez-Ojeda, María Angustias (Int J Environ Res Public Health, 2020)
The migrant population has increased in recent years and, as a result, so has cultural diversity. Universities are incorporating specific modules addressing cultural diversity. However, the native population has negative attitudes towards immigrants, as they believe that immigrants receive more social benefits and abuse healthcare services. Nurses may have these attitudes too, which may affect the way they treat patients. The objective of this study was to determine nursing students’ attitudes towards the rights of the migrant population. This is a descriptive ex post facto study using a cross-sectional design, with 821 nursing students in Melilla, Ceuta, and Almeria, Spain. An anonymous questionnaire was used for data collection. Students recognize the same rights for both the immigrant and native populations. More than 80% of the sample upholds the right of undocumented immigrants and their families to access publicly funded healthcare. Attitudes were more positive among students with a Berber background and first-year students. Students approved of the right of immigrants and their families to healthcare and education. The students’ negative attitudes towards the social rights of immigrants need to be addressed with intercultural training to reduce their prejudices as future professionals in a multicultural society.